Lingering in Leggoian Light: Contemplating Carl Leggo's Momentous Mentorship - Rajabali, Anar (Art/Research International)

(untitled) (University of Alberta, 2023)
My PhD supervisor and mentor, Carl Leggo, died of cancer on March 7th, 2019. In this essay, I trace the personal, poetic, intellectual, and spiritual journey of his momentous mentorship. In the absence of his physical being, there is still a profound presence, and what I have come to know as pedagogical light. On his passing, another lyrical lesson began for me on how what a teacher leaves behind can stay in the mind, heart, and soul for a lifetime. I have emerged knowing what it means to live poetically, as Carl was writing and teaching us all along. His mentorship is enduring and continues to shape the art of my own being into fullness as a poet, (re)searcher, and teacher. Here, through prose and poetry, I reflect on Carl’s wisdom and how he saw the breadth of my pedagogical being—the whole of the moon.